Formation Of Professional Pedagogical Competence of Future Primary School Teachers on The Basis of Creative Approach - Olimova Feruza Karimjanovna (Genius Journals, 2021)
The article stems from a theoretical and practical study of the role of student teaching in the formation of the foundations of professional competence of students in the system of higher professional education. Modern higher vocational training puts forward problems on formation of a wide spectrum professional competence graduates, and country high schools are interested to prepare the competitive experts claimed on a modern labour market.
Keywords: Professional competence graduates; pedagogical activity; comprehensive; extracurricular educational activities,